Absolutism of The Caliphate During the Abbasid Dynasty - Wina Arsita; Ellya Roza; Perisi Nopel (Pusdikra-Publishing.com, 2024)
The Abbasid Dynasty was the second Caliphate to rule Baghdad for more than five centuries (132H/750 AD to 656H/1258 AD) after conquering the Umayyad Caliphate against the background of the Umayyad Dynasty's oppression of the Abbasid Dynasty. During the five centuries of rule the Abbasid Caliphate reached its heyday in the field of science, both general science and religion. The Abbasid system of government refers to four aspects. In the first and third periods of Abbasid rule, Persian culture was greatly influenced and in this period more emphasis was placed on the cultivation of Islamic civilization and culture than territorial expansion. In the second and fourth periods influenced by Turkish culture which was very dominant in politics and government. While the fifth period was marked by the entry of the Seljuks into Baghdad until the fall of Baghdad to the Mongols. Each dynasty had its own style of leadership as well as the Abbasid Dynasty which applied absolutism in its leadership. Where the Caliph has authority over matters related to the state and religion. The caliph has unlimited authority and can only be replaced when the caliph dies.